2015
DOI: 10.5588/ijtld.14.0608
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of BCG in HIV-exposed and non-exposed infants following routine birth or delayed vaccination

Abstract: SUMMARY BACKGROUND Human immunodeficiency virus (HIV) exposed infants are at high risk of Mycobacterium tuberculosis exposure, have high rates of progression to tuberculosis (TB) disease and are at significant risk of bacille Calmette-Guérin (BCG) induced adverse events. OBJECTIVE To evaluate a delayed BCG vaccination strategy in HIV-exposed infants. DESIGN A randomised trial of routine BCG vaccination given at birth compared to 14 weeks of age in HIV-exposed non-infected and non-HIV-exposed infants to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…These data are consistent with our own and other published data. [5,23] The higher observed antibody responses to Hib and pertussis amongst HEU infants may be due to reduced maternal-infant placental antibody transfer in the presence of maternal HIV infection. Jones et al showed that HEU infants had lower concentrations of specific antibodies at birth than HUU infants to Hib, wP, pneumococcus and tetanus vaccines, in the identical study setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with our own and other published data. [5,23] The higher observed antibody responses to Hib and pertussis amongst HEU infants may be due to reduced maternal-infant placental antibody transfer in the presence of maternal HIV infection. Jones et al showed that HEU infants had lower concentrations of specific antibodies at birth than HUU infants to Hib, wP, pneumococcus and tetanus vaccines, in the identical study setting.…”
Section: Discussionmentioning
confidence: 99%
“…BCG coverage was estimated at 99% during 2005. [22] Eligibility and randomization Recruitment, enrolment, BCG vaccination and surveillance were carried out as previously described [23]. Briefly, this was an individual, single-blinded, exploratory randomized Phase 2 clinical trial investigating immunological effects of early versus delayed BCG vaccination in HIV-exposed and -unexposed infants (DOH-27-1106-1520).…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Leading candidate vaccines for either of pathogen have not been effective. However, these studies are not conclusive and reported contrasting findings [200][201][202][203][204]. It has become a necessity to recalibrate many fine intricacies of the immune system that were not prioritized earlier.…”
Section: Discussionmentioning
confidence: 96%
“…However, HIV+ infants not identified in infancy are at high risk for disseminated BCG. In South Africa, BCG induced immune responses at 52 weeks of age did not differ in HEU infants receiving the vaccine at birth compared to 14 weeks of age (36). A similar study is currently underway in Uganda (NCT02606526).…”
Section: Bcgmentioning
confidence: 91%